Contemporary relevance – a category of historical science and of the didactics of history and its consequences in teacher training (Yesterday & Today Journal for History Education in South Africa and abroad, 2021)
Contemporary relevance as a category of the didactics of history teaching includes not only historical facts which might be deemed the causes ofpresent-day problems and circumstances but also those which, on the grounds of the values or ideas inherent in them, are identical, equivalent, or contraryto present-day problems or notions. A context of meaning is created between present and past which gives rise to orientation knowledge, making it possibleto reflect on solutions to present-day problems, to think of alternatives to habitual contemporary patterns of thinking and living, and to developfuture perspectives. Selected examples of the various aspects of contemporary relevance are discussed, such as the conflict between Israelis and Arabs inthe Middle East, and the role of religion at various times in history. The consequences arising from this category for both the didactic and subjectspecific training of History teachers will be discussed, as well as the nature of the relationship between subject-specific and didactic training.
Keywords: Contemporary relevance; Context of meaning between present and past; History; Didactics of History; History teacher training; History lessons; Israel and the Palestinians; State and religion